Reasons and Victims of Honour Killing in Pakistan: An Analysis - Fozia Naseem; Asma Shakir Khawaja; Ishtiaq Ahmad Choudhry (Journal of Political Studies, 2019)
Honour killing in Pakistan is a very critical issue which is being echoed throughout the world. Parallel to it are the governmental claims that this issue has been addressed, by enhancing the representation in the legislature assemblies and by the strict and hard laws in this regard. However, this problem is the deeply rooted in socio-economic and cultural values and traditions of the country. The supporters of such values are sitting in the lawmaking bodies and openly support such negative practices. They have kept the doors open in the legal and judicial system for the escape of the offenders. Overwhelming majority of the victims are women of the remote rural areas, while the offenders are, mainly, the husbands, fathers or brothers. The reasons of this cruel practice, as found in this study are related to the alleged extra marital relations of the women (which never proved) or exercise of the choice of marriage by the victims, and very rarely the disputes of the property. Majority of the crimes remained unregistered, hence no question of the trial or the punishment. Major hindrances in the improvement of lack of women education, poverty, poor implementation system of law, poor grip/writ of the government in the remote rural areas of the country.